PELAKSANAAN PEMBELAJARAN VOKAL PADA KELAS IX DI MTsN 5 KOTA PADANG (Avant-garde: Jurnal Ilmiah Pendidikan Seni Pertunjukan, 2026)
This study aims to describe the implementation of vocal learning for ninth grade students in class IX.2 at MTsN 5 Kota Padang, particularly focusing on diaphragm breathing techniques and pitch accuracy (intonation). The study uses a qualitative approach with a descriptive method. Data collection techniques are carried out through observation, interviews, and documentation, while data analysis techniques include data reduction, data presentation, and drawing conclusions. The research results show that the implementation of vocal learning has been carried out through the stages of planning, implementation, and evaluation. The methods used in the learning process include lecturing, demonstration, and drills. Nevertheless, obstacles were still found in the learning process, namely that students were not yet able to control their diaphragm breathing properly and were not accurate in aiming the pitch. Thus, it can be concluded that the implementation of vocal learning in class IX.2 MTsN 5 Kota Padang has been carried out, but it has not optimally improved the students' vocal technique skills.